Breathing, Attention & Consciousness in Sync: The role of Breathing Training, Metacognition & Virtual Reality - Mitsea, Eleni; Drigas, Athanasios; Skianis, Charalampos (Technium Social Sciences Journal, 2022)
The purpose of the current review study is to shed light on the relationship between respiration and attention. Specifically, we examined whether and how respiration can provoke alterations in attentional states. Secondly, we investigated the benefits of breath-control training techniques in attention. Furthermore, we explored the effectiveness of virtual reality breathing training in improving respiration along with attention. Finally, we discussed the role of metacognition in the conscious synchronization of respiration with attention. It was revealed that every time respiration loses stability, attention fluctuates. Every time respiration is stabilized, attention finds steadiness. The results confirmed that respiration, attention, and as a result consciousness are characterized by bidirectional synchronization since their systems present coupling functions and dynamical interactions. It was also confirmed that breath control practices guarantee instant as well as long-lasting attentional improvements regulating all those mechanisms that strengthen mental alertness firing either the pathways of relaxation or excitation. Conscious-breath training is a practice of mindful metacognition that supports the coupling of attention with respiration. Metacognition in breathing utilizes respiration to improve attention but at the same time attention is used as a tool to consciously control breathing. Finally, breathing control training in virtual reality not only improves attention along with respiration but may finetune internal and external attention. This study concludes that breathing and attention are two ‘giant’ mechanisms that go hand-in-hand and carry on their ‘shoulders’ the whole cognition. Training conscious breathing via advanced technologies should be incorporated into the dialogue of education as methods for brain rewiring assuring better inclusion and academic achievement, especially for those with disabilities.